Ranganathan, The Man and His Works: View Through a Bibliography (Biography series 1) - Palmer, Bernard I. (Journal of Information and Knowledge, 2002)
Presents a review of the book Essay in personal bibliography. After pointing out that A K Das Gupta's career had well prepared him to compile a bibliography of the works by and on Dr S R Ranganathan, appreciatively comments on the helpful division of the text, the sequence and method of numbering of the chapters, and the classified arrangement of the entries. Draws attention to the usefulness of the Librametric Study in bringing out the pattern of distribution of the works by and on Ranganathan by subjects, by quantity, by Ian· guage, by period etc, and thereby leading one to examine the probable influencing factors for the particular pattern observed. Briefly mentions each of the major works of Ranganathan and its impact, commenting in particular the Five Laws of Library Science, Colon Classification, Classified Catalogue Code, Theory of Library Catalogue, Library Development Plans, and Library Legislation. Recalling his early association with Ranganathan, ille author adds personal touches to his statements, as when writing about Ranganathan's method of assigning a scale of priority to problems, the peripatetic discussions, interest in mysticism, and ambitious library development plans. Gives a glimpse of some aspects of Ranganathan's personality the sweep of his intellect, contributions to professional library periodicals, and encouragement of young librarians. Concludes with an appeal for updating the bibliography.